On the Monotonicity and Log-Convexity of a Four-Parameter Homogeneous Mean - Yang Zhen-Hang (Journal of Inequalities and Applications, 2008)
Abstract A four-parameter homogeneous mean is defined by another approach. The criterion of its monotonicity and logarithmically convexity is presented, and three refined chains of inequalities for two-parameter mean values are deduced which contain many new and classical inequalities for means.